Applied insight: studying reducing the carbon footprint of the drying process and its environmental impact and financial return - Ibrahim, Ayman; Amer, Alia; Elsebaee, Islam; Sabahe, Amr; Amer, Mariam A. (Frontiers in Bioengineering and Biotechnology, 2024)
Harnessing solar energy is one of the most important practical insights that have been highlighted to mitigate the severe climate change (CC) phenomenon. Therefore, this study aims to focus the light on the use of hybrid solar dryers (HSD) within an environmentally friendly framework, which is one of the promising applications of solar thermal technology to replace traditional thermal technology that contributes to increasing the severity of the CC phenomenon. The HSD based on traditional electrical energy source (HSTEE) and electrical energy from photovoltaic panels (HSPVSE) were evaluated compared to a traditional electrical (TE) dryer for drying some medicinal and aromatic plants (MAP). This is done by evaluating some of the drying outputs, energy consumed, carbon footprint, and financial return at 30, 40, and 50 °C. The best quality of dried MAP samples in terms of essential oil (EO, %) and microbial load was achieved at 40 °C. The HSTEE dryer has reduced energy consumption compared to the TE dryer by a percentage ranging from 37 to 54%. The highest CO2 mitigated ratio by using the HSTEE dryer was recorded at thyme, marjoram, and lemongrass samples with values ranging from 45 to 54% at 30, 40, and 50 °C. The highest financial return obtained from energy consumed reduction and credit carbon footprint is achieved at 50 °C with values ranging from 5313.69 to 6763.03 EGP/year in the case of using coal as a fuel source for the generation of electricity. Moreover, the HSPVSE dryer achieved a 100% reduction in traditional energy consumption and then reduced CO2 emissions by 100%, which led to a 100% financial return from both energy reduction and carbon credit. The highest financial returns were